2012
DOI: 10.1152/ajpheart.00965.2011
|View full text |Cite
|
Sign up to set email alerts
|

Dietary obesity increases NO and inhibits BKCa-mediated, endothelium-dependent dilation in rat cremaster muscle artery: association with caveolins and caveolae

Abstract: Howitt L, Grayson TH, Morris MJ, Sandow SL, Murphy TV. Dietary obesity increases NO and inhibits BK Ca-mediated, endothelium-dependent dilation in rat cremaster muscle artery: association with caveolins and caveolae. Am J Physiol Heart Circ Physiol 302: H2464 -H2476, 2012. First published April 6, 2012 doi:10.1152/ajpheart.00965.2011.-Obesity is a risk factor for hypertension and other vascular disease. The aim of this study was to examine the effect of diet-induced obesity on endothelium-dependent dilation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 78 publications
0
33
2
Order By: Relevance
“…Several studies in animal models of hypertension provide evidence that both supports and minimizes a role for BK channel dysfunction in hypertension. [6,7, 10-12,17-19] Studies in C57BL/6J BK β1-knockout mice do not support an association of vascular BK channel dysfunction with hypertension, as these mice are not hypertensive under normal conditions. [10-12] More recent work in high-fat fed rats and mice indicated that impaired BK channel function contributes to elevated BP through increased tone in resistance arteries, and that reduced BK β1-subunit expression plays a major role in obesity associated vascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies in animal models of hypertension provide evidence that both supports and minimizes a role for BK channel dysfunction in hypertension. [6,7, 10-12,17-19] Studies in C57BL/6J BK β1-knockout mice do not support an association of vascular BK channel dysfunction with hypertension, as these mice are not hypertensive under normal conditions. [10-12] More recent work in high-fat fed rats and mice indicated that impaired BK channel function contributes to elevated BP through increased tone in resistance arteries, and that reduced BK β1-subunit expression plays a major role in obesity associated vascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Animal models of metabolic disorders such as insulin resistance[14], diabetes[15], and genetic[16]or high-fat diet-induced obesity[17-19] also show vascular BK channel dysfunction. Reduced expression[17-19] or increased degradation of BK β1-subunit protein caused by oxidative signaling[14,15] appears responsible for vascular BK channel dysfunction, as α-subunit protein expression is unchanged. BK channel deficiency contributes to increased vascular tone and blood pressure regulation in these animal models of metabolic disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity is associated with increased circulating levels of cholesterol and leptin 34 . Cholesterol levels are higher in caveoli 35 , the location of hERG a-and b-subunit insertions 36 . Direct interaction may occur between membrane lipids and amino acids in membrane-traversing domains of ion channel proteins 37 , and hERG channel kinetics are sensitive to the cholesterol content of the plasma membrane 36 .…”
Section: Discussionmentioning
confidence: 94%